Grenzgänge und Grenzziehungen Transdisziplinäre Ansätze in der Lehrer*innenbildung - Brocca, Nicola; Ann-Kathrin, Dittrich; Kolb, Jonas (innsbruck university press, 2022)
In their daily work, teachers have to cope with a wide range of tasks, beside teaching in school. These include supporting learning processes, dealing with multilingualism and other forms of diversity, and using digital media. These different dimensions demand teachers to constantly confront numerous boundaries. This anthology is dedicated to discuss existing boundaries as well as border crossings in teacher education with special consideration given to approaches from the fields of didactics, educational sciences, and Islamic theology and religious education. The contributions of the volume depict the complexity of teacher education and offer innovative transdisciplinary perspectives.